Development of a prospective cohort of HIV Exposed Sero-Negative (HESN) individuals in Jos Nigeria. Issue 1 (December 2016) - Osawe, Sophia; Okpokoro, Evaezi; Datiri, Ruth; Choji, Grace; Okolo, Felicia; Datong, Pam; Abimiku, Alash'le
Abstract Background HIV/AIDS continues to be a global health problem. With currently no cure, it is critical to get an effective vaccine to add to the arsenal of prevention and treatment tools. HIV Exposed Sero-Negative (HESN) individuals were enrolled and followed for 2 years. Methods A prospective observational cohort study to enroll HESN volunteers and their partners was developed with a 2-year follow up. This was a vaccine preparedness study and designed as a Phase IIb trial. We provided counseling, lab testing and conducted medical examinations for all enrollees. Results A total of 534 HESN were enrolled with 48 % (256) females and 52 % (278) males, a mean age of 37 ± 9 years. Three female HESN enrollees seroconverted giving this cohort a HIV incidence rate [95 % coefficient interval (CI)] of 3.2 (2.3–4.2) per 100, 000 person-months of observation. Baseline analysis showed that female HESN are 24 % more likely to have their spouse consistently use condoms (RR 1.24;p = 0.04); 16 % more likely to have HIV+ partners with detectable viral load (RR 1.16, p = 0.03) and 28 % more likely that their HIV+ partners has a CD4 count less than 350cells/μl (RR 1.28, p = 0.03) when compared to male HESN. Conclusions Our findings suggest that female HESN are more at risk of HIV acquisition due the low CD4 counts and detectable viral load among their HIV+ spouses. Moreover, we provide additional information on incidence and risk factors among naturally exposed persons, which might impact biomedical prevention research and immune responses to HIV vaccines.